Examinning the Opinions of Students and Parents on Oral History Studies within the Scope of Life Sciences Lesson - Halil İbrahim SAĞLAM; Sinem SAYIMLI (Anı Publishing, 2021)
This research was conducted to determine the opinions of students and parents about oral history studies by examining journals kept by them within the scope of the primary school 3rd grade life sciences lesson. This research was held through an analytical research model. The data of the study were obtained from 28 journals selected by using criterion sampling method from a total of 34 individual journals, 17 of which were kept by primary school 3rd grade students and 17 belonged to the parents of these students, at a private education institution in the 2017-2018 academic-year. The data obtained were analyzed by content analysis method. In the research, from the journals kept within the scope of oral history studies, it was concluded that the students spend quality time with their family elders, listen to each other, try to understand each other, learn about their lives, compare the past with the present, feel like little historians, feel happy to know their family elders closely, experience empathy with family elders, and they started to comprehend change and continuity. In addition, it has been revealed that oral history improves students' skills such as expressing themselves, communicating, researching, using resources, and increasing their self-confidence and responsibility levels. It is recommended that oral history studies should be used in life sciences lessons due to their contribution to students' learning their backgrounds and improving their skills.